2017
DOI: 10.1002/14651858.cd011897.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Umeclidinium bromide versus placebo for people with chronic obstructive pulmonary disease (COPD)

Abstract: Umeclidinium reduced acute exacerbations requiring steroids, antibiotics, or both, although no evidence suggests that it decreased the risk of hospital admission due to exacerbations. Moreover, umeclidinium demonstrated significant improvement in quality of life, lung function, and symptoms, along with lesser use of rescue medications. Studies reported no differences in adverse events, non-fatal serious adverse events, or mortality between umeclidinium and placebo groups; however, larger studies would yield a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…16 Although the findings from randomised controlled trials (RCTs) appear to be reassuring about the cardiovascular safety of long-acting bronchodilators, the trials were usually underpowered for safety endpoints, and patients with pre-existing cardiovascular disease and other comorbidities were frequently excluded. 17 Metaanalyses of those RCTs have also had limited power to examine cardiovascular risk [9][10][11][12][13][14][15] and the authors of one review 9 reported they were unable to undertake a metaanalysis of serious cardiovascular events because of a lack of consistency in reporting those outcomes. These limitations have prompted calls for more inclusive RCTs, as well as large observational studies, in real-world settings of clinical care.…”
Section: Key Messagesmentioning
confidence: 99%
“…16 Although the findings from randomised controlled trials (RCTs) appear to be reassuring about the cardiovascular safety of long-acting bronchodilators, the trials were usually underpowered for safety endpoints, and patients with pre-existing cardiovascular disease and other comorbidities were frequently excluded. 17 Metaanalyses of those RCTs have also had limited power to examine cardiovascular risk [9][10][11][12][13][14][15] and the authors of one review 9 reported they were unable to undertake a metaanalysis of serious cardiovascular events because of a lack of consistency in reporting those outcomes. These limitations have prompted calls for more inclusive RCTs, as well as large observational studies, in real-world settings of clinical care.…”
Section: Key Messagesmentioning
confidence: 99%
“…There is also concern that long‐acting bronchodilators (long‐acting muscarinic antagonists [LAMAs] and long‐acting beta2‐agonists [LABAs]) might increase the risk of acute coronary events still further [ 7 ]. This is important because coronary events are responsible for more deaths than respiratory failure in patients with COPD [ 8 ] and meta‐analyses of randomised controlled trials (RCTs) have found that the use of long‐acting bronchodilators (as mono‐therapy [ 9 , 10 , 11 , 12 ] or dual therapy [ 13 , 14 , 15 ]) is associated with relatively small patient‐relevant benefits. Moreover, successive updates of the Global Initiative for Chronic Obstructive Lung Disease guidelines [ 16 ] and a recent American Thoracic Society clinical practice guideline [ 17 ] have recommended the combined use of a LAMA and LABA in patients whose symptoms are not well controlled.…”
Section: Introductionmentioning
confidence: 99%